Mégare et les établissements mégariens de Sicile, de la Propontide et du Pont-Euxin. Histoire et institutions - Robu, Adrian (Peter Lang International Academic Publishing Group, 2014)
This book aims to offer a new interpretation of the settlement movement initiated by the city of Megara in archaic times. It shows the role of conflict between the aristocratic families for the departure of the Megarians and reveals the role of the heritage of the metropolis in the creation of institutions of colonial cities.